Behavioral Patterns of Depression Patients and Control Population (2022)
Behavioral and multifactorial factors, such as psychological, nutritional, dental pathology, and physical activity habits, are factors that control depression. The objective of the present study was to analyze the differences in the behavioral, psychological, nutritional, dental pathology, and physical activity patterns of the depressed and control population. Forty-eight participants with depression (45.7 +/- 12.0) and one hundred participants in a control group without any pathology or medication (48.9 +/- 7.9) were interviewed using an online questionnaire. The multifactorial items of psychology, oral behavior, nutritional habits, and physical activity profile were analyzed through a set of questionnaires. The results showed how the depression group showed significantly higher psychological measures related to personality, anxiety, depression, loneliness, perceived stress, and psychological inflexibility than the control group. The control group showed significantly higher weekly vitality, vitality at the end of the week, weekly frequency of juice, wine, coffee, fresh vegetable salad, and Bristol scale than the depression group. Higher values of migraine headache, weekly soft drink frequency, and digestion after meals were found in the depression group. In addition, patients with depression also presented poor dental health, presenting higher rates of gastritis or heartburn, dry mouth, dental sensitivity, and sick days per year than the control group. Both groups presented a pattern of low physical activity. This information allows a better understanding of a multifactorial disease, as well as the creation of intervention and prevention protocols for this disease at a behavioral and lifestyle level.